Climate Changes Due to the Burning of Gas Associated with Oil Operations in Basra Province - Potrous , Saad M. (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
Air Pollution, addition of harmful substances to the atmosphere resulting in climate change and damage to the environment, human health, and quality of life. In this work, measurement of air pollutants was conducted in three regions in Basra Province as follows; (1)- Basra University, Garma Site. (2) Al- Gemaeit Site. (3)- Abi Al-Khaseeb Site The measurements of air pollutants [ CO2 , H2S, SO2, O3, CO, THC ] values have been obtained from the General Directorate for Environment Protection and Improvement in the Southern Region of Iraq. The results of this research project showed that the value of the pollutant sulfur dioxide (SO2) reached the highest value which is (0.1393 ppm) compared with the National Ambient Air Qualit y Standards which is (0.04 ppm) in the Al- Gemaeit Site. Likewise, the Total Hydrocarbons (THC) reached in higher values for all the regions under study, where the maximum value at Basra University, Garma Site reached to maximum value which is (16.53 ppm) compared with the National Ambient Air Quality Standards which is (3 ppm). It is possible to conclude the transferring winds are pushed the pollutants to Basra City and the climate change can affect by air quality, and certain air pollutants can affect climate change and that contributes to climate change by trapping heat in the atmosphere.